A REPLY BY PROFESSOR GREER. - Greer, Howard C. (The Accounting Review, 1937)
Abstract The article focuses on the statement of accounting principles by the American Accounting Association, published in the June 1936 issue of the journal The Accounting Review. The article presents comments in support of the suggested principles. In developing certain principles that would be sound in theory and practical in application, adoption of the best of current practice is involved, but with modifications designed to remove some of the uncertainties and inconsistencies from corporation income statements. Particularly it is sought to eliminate present confusion about the unusual cost or revenue items which sometimes are treated as capital losses or gains, sometimes as adjustments of earned surplus for prior years, and sometimes as current profit and loss charges. It is suggested that all the amortized costs and all the realized gains should be recognized in the income statement of some year, either as special items in the statements for the current year, or through correction and rewriting of the statement for prior years.